Fusarium-damaged kernels and deoxynivalenol in Fusarium-infected U.S. winter wheat - Jin, Feng; Bai, Guihua; Zhang, Dadong; Dong, Yanhong; Ma, Lingjian; Bockus, William W.; Dowell, Floyd E. (My University, 2014)
Fusarium head blight (FHB) is a devastating disease that threatens wheat (Triticum aestivum) production in many areas worldwide. FHB infection results in Fusarium-damaged kernels (FDK) and deoxynivalenol (DON) that dramatically reduce grain yield and quality. More effective and accurate disease evaluation methods are imperative for successful identification of FHB-resistant sources and selection of resistant cultivars. To determine the relationships among different types of resistance, 363 (74 soft and 289 hard) U.S. winter wheat accessions were repeatedly evaluated for FDK and DON concentration in greenhouse and field experiments. Single-kernel near-infrared (SKNIR)-estimated FDK and DON were compared with visually estimated FDK and gas chromatography-mass spectroscopy-estimated DON. Significant correlations were detected between percentage of symptomatic spikelets and visual FDK in the greenhouse and field, although correlations were slightly lower in the field. High correlation coefficients also were observed between visually scored FDK and SKNIR-estimated FDK (0.72, P < 0.001) and SKNIR-estimated DON (0.68, P < 0.001); therefore, both visual scoring and SKNIR methods are useful for estimating FDK and DON in breeding programs.
Citation: Jin, Feng, Guihua Bai, Dadong Zhang, Yanhong Dong, Lingjian Ma, William Bockus, and Floyd Dowell. “Fusarium-Damaged Kernels and Deoxynivalenol in Fusarium-Infected U.S. Winter Wheat.” Phytopathology™ 104, no. 5 (January 8, 2014): 472–78. https://doi.org/10.1094/PHYTO-07-13-0187-R.
Keywords: Fusarium head blight; Winter wheat; Wheat; Triticum aestivum; Fusarium-damaged kernels; Deoxynivalenol